Modelos de innovación en gestión del talento humano (2019)
The purpose of this document is to present the history of human management and its progress by means of different models and approaches of different authors. The work focuses on innovation processes and how they have marked the progress of organizations in order to improve the quality of life of employees. The paper also proposes new models that have emerged from the different needs of organizations to improve their areas of talent or human management.